Complete mitochondrial DNA sequence of Norwegian skates (Raja brachyuran Lafont, 1871) imported to Korea. Issue 3 (4th March 2021) - Kim, Moo-Sang; Kim, Jinho; Kang, Tae-Wook; Jeong, Uiseok; Kim, Kang-Rae; Bang, In-Chul
Abstract: In this study, the complete mitochondrial genome of Norwegian skates imported to Korea was sequenced with a circular molecule of 17, 121 bp, which consisted of 13 protein-coding genes (PCGs), 2 ribosomal RNAs, 22 transfer RNA genes, and a control region (D-loop). And among these sequences, 193 bp sequence in the D-loop of the genus Raja suggested the possibility of being used as a genetic marker for classification of Raja and Dipturus species. The BI phylogenetic tree by using the nucleotide sequences of 13 PCGs from 15 available mitogenomes of family Rajidae confirmed also that Norwegian skates imported to Korea form a group with Raja brachyura species with high branch value, and that this was a species of Raja brachyura . As above, these results would be expected to provide for the further understanding on the phylogenetic relationship, taxonomic classification and phylogeography of the family Rajidae.